In vitro assessment of growth kinetics and differentiation potential of bone marrow derived mesenchymal and fetal fibroblast cells of caprine - KUMAR, DHARMENDRA; SINGH, AJIT PRATAP; PATEL, PRIYANKA; SINGH, RANDHIR; SARKHEL, BIKASH CHANDRA (The Indian Journal of Animal Sciences, 2016)
The present study assessed comparative growth kinetics and differentiation potential of mesenchymal and fetal fibroblast cells of goats in vitro. The mesenchymal cells were isolated from bone marrow and fibroblasts were obtained from skin of 3–4 months old fetus. During culture, more than 99% viability of both cell groups indicated optimum culture conditions for in vitro experiments. The population doubling time (PDT) of BM-MSCs and FFCs were similar at third (18.25±0.05 and 18.41±0.07) and seventh (19.61±0.06 and 19.68±0.12) passages. But at 12th passage, FFCs cells had a significantly higher PDT (35.77±0.68 vs 32.063±1.0) as compared to BM-MSCs. Both groups of cells showed a characteristic sigmoid curve on plotting cell concentration verses days of culture. The stem cell like property was exhibited by BM-MSCs by differentiating into osteoblast, chondrocytes and adipocytes under specific media, which were further confirmed by specific staining of cells. Also, the BM-MSCs showed colonogenic property by forming different number of clones at third (60.5±0.59), seventh (56.6±0.5) and 12th (33.4±0.45) passages. The fetal fibroblast cells did not exhibit colonogenic and differentiation potentials. This study concluded that although BM-MSCs and FFCs shared similar morphology and growth kinetics during initial passages but FFCs does not exhibit the stem cell like properties in terms of differentiation potency.